First-principles study of the Σ3(112) grain boundary in Fe-rich Fe-Cr alloys. (May 2020) - Yang, Yaochun; Schönecker, Stephan; Li, Wei; Wang, Ci; Huang, Shaosong; Zhao, Jijun; Vitos, Levente
Abstract: We report a first-principles investigation of the Σ3(112) grain boundary (GB) in body-centered cubic Fe-rich Fe1- x Cr x alloy as a function of chemical composition and temperature. The equilibrium amount of Cr at the GB undergoes a sharp transition from slight enrichment in low-alloyed Fe-Cr ( x ≤ 0.06–0.08) to complete Cr saturation for 0.08 ≤ x ≤ 0.15. The GB chemistry at room-temperature and below is characterized by miscibility gaps, destabilizing a Fe-Cr interfacial solid solution towards decomposition into Fe-rich and Cr-rich clusters. The Cr-rich clusters at the GB may serve as nucleation centers for secondary phases in Fe-Cr alloys. Graphical abstract: Image, graphical abstract